Big Data in strategic management accounting - S.F.; T.O.; O.M. (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу, 2023)
The importance of the influence of Industry 4.0 and the digitalization of the economy on the development of the accounting system in modern conditions has been grounded. The role of Big Data in solving key accounting problems and increasing the relevance of accounting information has been grounded. The reasons for the relevance of using Big Data in management accounting have been analyzed. The problems caused by using Big Data in management accounting have been identified and analyzed. The need to develop management accountants’ abilities and skills in data processing and presentation using Big Data tools has been grounded. The role of big data in ensuring the digital transformation of the enterprise’s strategic management system has been analyzed. Directions for using Big Data in strategic management accounting have been identified and described (innovative development of the system; improvement of strategic control; improvement of particular accounting methods; improvement of accounting methodology; change in the role of strategic management accountants).